Synchronous shedding of multiple bat paramyxoviruses coincides with peak periods of Hendra virus spillover. Issue 1 (1st January 2019) - Peel, Alison J.; Wells, Konstans; Giles, John; Boyd, Victoria; Burroughs, Amy; Edson, Daniel; Crameri, Gary; Baker, Michelle L.; Field, Hume; Wang, Lin-Fa; McCallum, Hamish; Plowright, Raina K.; et al.
ABSTRACT: Within host-parasite communities, viral co-circulation and co-infections of hosts are the norm, yet studies of significant emerging zoonoses tend to focus on a single parasite species within the host. Using a multiplexed paramyxovirus bead-based PCR on urine samples from Australian flying foxes, we show that multi-viral shedding from flying fox populations is common. We detected up to nine bat paramyxoviruses shed synchronously. Multi-viral shedding infrequently coalesced into an extreme, brief and spatially restricted shedding pulse, coinciding with peak spillover of Hendra virus, an emerging fatal zoonotic pathogen of high interest. Such extreme pulses of multi-viral shedding could easily be missed during routine surveillance yet have potentially serious consequences for spillover of novel pathogens to humans and domestic animal hosts. We also detected co-occurrence patterns suggestive of the presence of interactions among viruses, such as facilitation and cross-immunity. We propose that multiple viruses may be interacting, influencing the shedding and spillover of zoonotic pathogens. Understanding these interactions in the context of broader scale drivers, such as habitat loss, may help predict shedding pulses of Hendra virus and other fatal zoonoses.